Linking pre-service teacher fitness and clarity of instruction to student skill acquisition in physical education class - Zakiah Noordin; Mohamad Nizam Nazarudin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of this research is to investigate the relationships between pre-service physical education (PE) teachers’ fitness, their clarity of instruction, and the skill acquisition of secondary school students in PE classes. The sample consists of 653 secondary school students aged 15-18 years from multiple schools across different districts in one of the states of Malaysia. Pre-service PE teachers involved were 60 students of a faculty of education from one of the Malaysian Public Universities. The instruments are self-administered questionnaires: 1. PE Teacher Fitness Questionnaire (TFQ), 2. Clarity of Instruction in PE Scale (CIPS), 3. Student Skill Acquisition Scale (SSAS). The scales Cronbach’s alpha values are between 0.812 and 0.893. Descriptive statistics and Pearson’s correlation analyses were performed using SPSS version 29. The results indicated. There were strong positive correlations between the pre-service PE teachers’ fitness (r = 0.872), clarity of instruction (r = 0.949), and the student’s skill acquisition in PE classes. These findings underscore the importance of incorporating comprehensive fitness and effective communication training into pre-service PE teacher education programs. Also, suggested avenues for further research and policy development aimed at optimising educational outcomes in physical education settings.